JOB SATISFACTION RELATIONSHIP WITH TURNOVER INTENTION - Tina Rakhmitania (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
This study aims to determine the relationship between job satisfaction and turnover intention at Ummi Hospital This type of research is quantitative and descriptive with an associative method which aims to see how much job satisfaction (X) has on turnover intention (Y) at Ummi Hospital. The population in this study were all employees with a total of 628 people, the sample was taken using the Slovin formula, and a sample of 268 people was obtained. This study uses quantitative methods with a questionnaire as a research instrument. The data analysis technique uses the help of data processing using the help of data analysis software. The results showed that the job satisfaction variable was significantly related to the employee turnover intention variable. This can be seen from the p-value of the relationship between job satisfaction and turnover intention = 0.000 which is smaller than the p-value = 0.05. It can be concluded that there is a relationship between the level of job satisfaction and turnover intention. Based on the results of the study, the researchers suggested that UMMI Hospital give more attention to improving supervision through activities of guidance, direction, observation, motivation and evaluation of employees, an objective performance appraisal system, and also creating a conducive work environment, to further increase employee job satisfaction.